PENERAPAN ETIKA BISNIS SYARIAH DAN DAMPAKNYA TERHADAP LOYALITAS PELANGGAN PADA YAYASAN AQIQOH NURUL HAYAT SURABAYA - Maharti, Resti Kartika; Fahrullah, Arasy (Jurnal Ekonomika dan Bisnis Islam, 2021)
The purpose of this study was to determine how the application of Islamic Business Ethics and its impact on customer loyalty at the Aqiqah Nurul HayatSurabaya. This study uses a qualitative method. The purpose of using qualitative methods is to understand the phenomenon of what is experienced by research subjects, in the subject under study there are several types of data, namely internal and external, in internal subjects, namely employees in the Operational Division who are in charge of carrying out Operational Marketing activities at the Aqiqah Nurul HayatSurabaya, while the external data subject is the customers of the Aqiqah Nurul HayatFoundation Surabaya. Another external research subject is a customer who has subscribed to or purchased Aqiqah services at the Aqiqah Nurul HayatSurabaya to provide information on how to implement Islamic Business Ethics at the Aqiqah Nurul HayatSurabaya. Collecting data in this study using interview techniques to find out and get the desired data followed by documentation techniques and direct observation. The results of this study indicate that the application of Islamic Business Ethics has a significant impact on increasing customer loyalty of the Aqiqah Nurul Hayatsuch as customer satisfaction through honest employee performance and paying attention to the halalness of the products being sold.